Kesempatan Investasi memoderasi profitabilitas dan likuiditas terhadap kebijakan dividen - Wulan Kusumadyaningrum (Politeknik Ganesha Medan, 2022)
Dividend policy is an increase in investor confidence in the company because investors perceive that the company is running better so that it can reduce investors' sense of uncertainty in investing their capital in the company. This study aims to analyze the effect of profitability, liquidity on dividend policy with investment opportunities as moderating variables. The population in this study were all manufacturing companies on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample selection used purposive sampling technique. Based on this technique, obtained 19 samples of companies with 57 units of analysis. The data in this study can be collected using documentation techniques. The data analysis tool in this study used descriptive statistics and multiple regression, namely the absolute value test on the SPSS 26 application. The results showed that profitability had no significant effect on dividend policy. On the other hand, where liquidity has a significant positive effect on dividend policy. Then the investment opportunity variable significantly moderates the effect of profitability and liquidity on dividend policy. In this study, the researcher provides suggestions for further researchers to add other variables, because in this study the independent variables still have a low influence on dividend policy. In addition, further researchers can also adjust other research objects according to their conditions.